Assessment of the efficacy and safety of lapatinib in combination with capecitabine in patients with metastatic HER2-positive breast cancer treated in Centrum Onkologii Ziemi Lubelskiej - Starosławska, Elżbieta; Czerepińska, Anna; Chrzanowska-Kapica, Agata; Czarnocki, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2010)
Background: Introduction of targeted therapy in the treatment of HER2-positive breast cancer patients had a favourable impact on prognosis in this patient population [1-7]. Lapatinib, a small molecule tyrosine kinase inhi-bitor directed against the intracellular HER2 and HER1 receptor domain, is indicated in combination with capecitabine in patients with HER2-positive advanced breast cancer who have progressed after therapy with trastuzumab-containing regimens [6, 7]. Aim of the study: Assessment of the efficacy and safety of lapatinib in combination with capecitabine in patients with HER2-positive metastatic breast cancer treated in Centrum Onkologii Ziemi Lubelskiej (COZL). Material and methods: Women with HER2-positive metastatic breast cancer who have progressed after therapy with anthracycline-, taxane-, and trastuzumab-containing regimens were treated with lapatinib (1,250 mg daily) and capecitabine (2,000 mg/m 2 days 1–14 of a 21-day cycle). Patients were analysed for response to treatment, time to progression, overall survival and tolerability. Results: From 1 August 2007 to 30 September 2009, 35 patients were treated. Treatment efficacy was assessed in 34 patients and tolerability in 35 patients. The median treatment duration was 6.1 months. Partial remission (PR) was observed in 5 (14.7%) patients, complete remission (CR) in 1 (2.9%) patient, and stable disease (SD) in 19 (55.9%) patients. Clinical benefit was observed in 17 (50.0%) patients. The median time to progression was 5.65 months. The median overall survival was not reached; in the analysed group 16 (45.7%) patients died. Adverse events were observed in 24 (68.6%) patients, including grade 3 or 4 adverse events in 8 (22.9%) patients. The treatment was interrupted due to toxicity in 3 cases. The most common adverse events were erythrodysesthesia (40%), diarrhoea (31.4%), asthenia (17.2%) and liver toxicity (17.2%). Conclusions: Lapatinib in combination with capecitabine is a valuable treatment option in HER2-positive metastatic breast cancer patients who have progressed after treatment with trastuzumab-containing regimens with acceptable toxicity.